Implementation of Enterprise Resource Planning at CV. Dewi Bulan - Wrestra Saridewi, Putu Putri; Putra, I Ketut Gede Darma; Sukarsa, I Made (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2021)
Nowadays, the development of information technology is very fast, which allows many companies to receive the latest information technology to support the smooth running of the company's business. CV. Dewi Bulan is a small and mediu enterprise (UKM) that produces incense stick. The problems that faced by CV. Dewi Bulan is an inefficient business process, its business activities are still manually recorded, documents related to the sale, production and purchase of raw materials are still handwritten on a form in the company and the bookkeeping is done once a month. These documents cannot be accessed in real-time. This problem causes delays in processing of customer orders. The solution to overcome this problem above is to implement Enterprise Resource Planning, where in practice, ERP can automate business practices and company business procedures. ERP implementation uses a technology that is using Odoo version 11.0. This research method consists of six stages of the research process, namely; literature study, data collection, data processing, application modeling, system testing >and implementation, also conclusions and suggestions as well. The final stage in this research is to conduct a survey with the UAT questionnaire and a Likert scale to assess the satisfaction level of Odoo application users. The results of the questionnaire were dominated by the assessment of "Satisfied", this indicate that the business improvement process is made were acceptable and applied in CV. Dewi Bulan. Keywords: Business Process, Enterprise Resource Planning, Odoo, Likert Scale, UAT.